Experimental study of working processes of low-speed long-stroke lubrication free piston compressor stages at high discharge pressure to suction pressures - V. L. Yusha; S. S. Busarov; A. V. Nedovenchany; R. Yu. Goshlya (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2018)
Theoretical studies of working processes of slow-speed reciprocating compressor stages with linear drive, carried out by the authors of this work, there is determined the necessity of experimental confirmation of the possibility of gas compression in one stage up to a pressure of 10,0 MPa and higher at atmospheric suction pressure. The paper presents the results of testing the newly developed low-speed piston compressor stage with a linear hydraulic drive with a ratio of discharge pressure to suction pressure from 50 to 100